Screening Ammonium‐Based Cationic Additives to Regulate Interfacial Chemistry for Aqueous Ultra‐Stable Zn Metal Anode - Leilei Zheng; Huihua Li; Mingbo Gao; Keer Huang; Jian Wang; Long Su; Lei Li; Hongzhen Lin; Xinpei Gao; Zhengqing Liu; Huang Zhang (Advanced Science, 2024)
Abstract The interfacial dynamics and chemistry at the electrolyte/metal interface, particularly the formation of an adsorption interphase, is paramount in dictating the reversibility of Zn metal deposition and dissolution processes in battery systems. Herein, a series of different cationic ammonium‐based electrolyte additives are screened that effectively modulate the interfacial chemistry of zinc anodes in aqueous electrolytes, significantly improving the reversibility of Zn metal plating/stripping processes. As initially comprehensive investigation by combining theoretical calculation and molecular dynamic simulation, the tetramethylammonium cation, with its specific molecular structure and charge distribution, is identified as pivotal in mediating the Zn(H2O)62+ solvation shell structure at the electrode/electrolyte interface and shows the strong resistance against electrolyte corrosion as revealed by X‐ray and optical measurements. As a result, the Zn||Zn symmetric cell with optimal electrolyte lasts for over 4400 h of stable plating/stripping behaviors, and the Zn||Cu asymmetric cell stabilizes for 2100 cycles with an average Coulombic efficiency of 99.8%, which is much better than the‐state‐of‐art progress. Consequently, full‐cells coupled with various cathodes showcase improved electrochemical performance, displaying high capacity‐retention and low self‐discharge behaviors. These findings offer essential insights of cationic additives in ameliorating zinc anode performance.